Впровадження інноваційної діяльності як рушійний фактор конкурентоспроможності підприємства - Тимофеєв, Володимир Миколайович; Масюк, В. М. (НТУ "ХПІ", 2010)
В статье рассматривается необходимость внедрения инноваций, как движущей силы конкурентоспособности предприятий, а также принципы инновационной политики и адаптации предприятия к переменам на рынке путем внедрения определенных мер во время проведения инновационной деятельности.

In the article the necessity of introduction of innovations is considered, as motive force of competitiveness of enterprise, and similarly basic principles of innovative policy and adaptation of enterprise to the changes at the market by the use of certain measures during introduction of innovative activity.
Keywords: інноваційна політика; інноваційна стратегія; інноваційна активність; науково-технічні роботи; високоефективне планування; адміністративно-командна система